FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN STROKE PADA PASIEN DI RSU H. SAHUDIN KUTACANE KABUPATEN ACEH TENGGARA - Khairatunnisa Khairatunnisa (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2017)
ABSTRACT Stroke is the first cause of disability and the third cause of death in the world both in developed and developing countries after heart disease and cancer.Based on the result of Basic Health Research in 2013, it was found out that there was the increase of stroke prevalence per 100,000 persons in Indonesia from 830 in 2007 to 1,210 in 2013. The purpose of this analytical observational study with case-control design was to find out the correlation of the factors of hypertension, diabetes mellitus, smoking, obesity, alcohol and family history of disease on the incident of stroke in the patients at H. Sahudin General Hospital Kutacane Aceh Tenggara District.This research was observational analytic with case control design. The case population is all stroke patients who seek treatment at RSU H. Sahudin Kutacane Aceh Tenggara District. The number of samples were 45 cases and 45 controls, with case and control ratio 1: 1, so the total sample was 90 people performed by matching age and sex. Case samples were taken by purposive sampling and control samples were taken by consecutive sampling. The data obtained were analyzed through univariate and bivariate using chi square test.The result showed the factors that significantly related to the incident of stroke were hypertension (OR = 4.67; 95% CI: 1.78 - 12.23) and diabetes mellitus (OR = 2.67; 95% CI: 1.01 - 7.04). The factors that did not significantly related to the incident of stroke were smoking, obesity, alcohol consumption and family history of disease.Expected to H. Sahudin General Hospital Kutacane should socialize the risk factors and the prevention of stroke to the patients through direct extension or various other media also adds CT-Scan facility. The community members are expected to be aware to visit the health service facility have their health checked routinely, always control their blood pressure and blood sugar level and to get accustomed to practicing health lifestyle and physical activity to prevent the stroke. Keywords: Stroke, Risk Factor